2020
DOI: 10.14740/cr1079
|View full text |Cite
|
Sign up to set email alerts
|

Low-Density Lipoprotein Cholesterol Targets in Patients With Coronary Heart Disease in Extremadura (Spain): LYNX Registry

Abstract: Background: Low-density lipoprotein cholesterol (LDL-C) contributes decisively to the development of cardiovascular disease (CVD). In the LYNX registry we determined the rate of achievement of the target value of LDL-C, the use of lipid-lowering therapy (LLT) and the predictive factors of not reaching the target in patients with stable coronary heart disease (CHD). Methods: LYNX included consecutive patients with stable CHD treated at the University Hospital of Caceres, Extremadura (Spain) from September 2016 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 44 publications
0
0
0
Order By: Relevance
“…In the current study, a higher proportion of patients with diabetes mellitus attained the recommended LDL-C goal compared with patients without diabetes, which is in agreement with many studies, including the Spanish LYNX and REPAR studies and the international CEPHEUS and DYSIS II studies, among others [13,15,25,26,31,38]. These findings suggest that clinicians may be paying more attention to CV risk factors management in diabetic patients in the real-world setting.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…In the current study, a higher proportion of patients with diabetes mellitus attained the recommended LDL-C goal compared with patients without diabetes, which is in agreement with many studies, including the Spanish LYNX and REPAR studies and the international CEPHEUS and DYSIS II studies, among others [13,15,25,26,31,38]. These findings suggest that clinicians may be paying more attention to CV risk factors management in diabetic patients in the real-world setting.…”
Section: Discussionsupporting
confidence: 91%
“…We found an overall achievement rate for the risk-based LDL-C goals of only 31.1%, despite all patients being on high-intensity statins, even with 62% of them on combination therapy of high-intensity statins plus ezetimibe. Regardless of differences in the recommended LDL-C targets, baseline CV risk of patients, or LLT used for CVD prevention, our findings are consistent with several international and Spanish studies that have consistently reported low rates of LDL-C goal attainment in high-or very high-risk patients, ranging from 4% to 57% [6,[10][11][12][13][14][17][18][19][20][21][22][23][24][25][26]. It must be highlighted that most patients included in the TERESA study were categorized as very high CVD risk as they were recruited in cardiology and internal medicine units.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations